Cechy i kompetencje audytora wewnętrznego - Bednarek, Piotr (Qualifications of an internal auditor, 2008)
"The increasing scope of modern internal auditing results in higher qualifications requirements for successful internal auditor. In Poland it seems insufficient to find and hire adequate person as an internal auditoronly on the basis of suggested qualifications specified in the public finance act and internal auditing standards. Thus in this paper the author attempted at identifying personal and professional qualifications of an internal auditor, who can be able to live up to today’s challenges in every organization."
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 15, s. 21-28